4touch Studio & Art Enterprise / Muhammad Nizam Mahmadi ... [et al.] - Mahmadi, Muhammad Nizam; Azizan, Azilawati; Syed Abas, Sharifah Hafzan; Hussain, Hasrol Nizam; Selamat, Abdullah (Faculty of Office Management & Technology, 2004)
4Touch Studio & Art Enterprise is fully Bumiputera Company that is trying to venture in the business of graphic design that has been monopolized by other races in the country. Malaysia provides many facilities and opportunities especially for bumiputeras for becoming entrepreneurs. As a Malaysian citizen, who will go through the era of information technology with the stable economic, political and social condition we should take the challenge given to us.